Long Swings in the Role of Government: An Analysis of Wars and Government Expenditures in Western Europe since the Eleventh Century - Ronald W.Crowley (Queen's University, Department of Economics, 1970)
In 1914, Henri Pirenne argued that, beginning in the eleventh century, Western European capitalism can be characterized by alternating periods of laisser-faire and public control. This paper attempts to judge the validity of Pirenne's hypothesis.
Keywords: 330